2015
DOI: 10.1111/boj.12357
|View full text |Cite
|
Sign up to set email alerts
|

Is post-polyploidization diploidization the key to the evolutionary success of angiosperms?

Abstract: Advances in recent years have revolutionized our understanding of both the context and occurrence of polyploidy in plants. Molecular phylogenetics has vastly improved our understanding of plant relationships, enabling us to better understand trait and character evolution, including chromosome number changes. This, in turn, has allowed us to appreciate better the frequent occurrence and extent of polyploidy throughout the history of angiosperms, despite the occurrence of low chromosome numbers in some groups, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(132 citation statements)
references
References 39 publications
3
127
2
Order By: Relevance
“…Increases in net diversification rates tend to follow a lag phase post-polyploidisation, adding support to the previously proposed model (Schranz et al 2012;Tank et al 2015). It therefore seems probable that at the genomic level the progression of events associated with diploidisation is an important factor in understanding the lag phase (Dodsworth et al 2016a).…”
Section: Introduction Polyploidy In Angiospermssupporting
confidence: 74%
See 2 more Smart Citations
“…Increases in net diversification rates tend to follow a lag phase post-polyploidisation, adding support to the previously proposed model (Schranz et al 2012;Tank et al 2015). It therefore seems probable that at the genomic level the progression of events associated with diploidisation is an important factor in understanding the lag phase (Dodsworth et al 2016a).…”
Section: Introduction Polyploidy In Angiospermssupporting
confidence: 74%
“…Some allopolyploids are recent and have no close polyploid relatives, whereas others appear to be much older and numerous, the result of speciation at the polyploid level. Polyploidy and diploidisation have been the subject of study in the genus for around two decades: chromosome arm translocations (Lim et al 2004), homoploid hybridisation , intergenic recombination , concerted evolution , long-term diploidisation of genomic repeats (Clarkson et al 2005;Dodsworth et al 2016a), progenitor determination (Kelly et al 2013), maternal genome donors , elimination of genomic repeats (Renny-Byfield et al 2011), the phylogenetic signal in repeats (Dodsworth et al 2015(Dodsworth et al , 2016b, floral evolution (McCarthy et al 2015), morphological character evolution (Marks et al 2011a;McCarthy et al 2016), biogeography (Ladiges et al 2011) and genome size changes (Leitch et al 2008). An earlier paper (Clarkson et al 2005) focused on the timing of polyploid events for a subset of polyploids in Nicotiana, using nonparametric rate smoothing (NPRS), but recent advances in molecular clock analysis make another study of this subject in the genus as a whole timely.…”
Section: Polyploidy In Nicotianamentioning
confidence: 99%
See 1 more Smart Citation
“…These reports strengthen the WGD Radiation Lag-Time Model formalized by Schranz et al (2012), who found that in six examples of angiosperm radiations a species-poor sister-group shared a WGD event with the species-rich crown group, directly contradicting the notion that WGD was the sole immediate cause of these radiations. The lag between WGD and subsequent radiations thus has been proposed as evidence that the long and stochastic process of polyploid drop is the proximal engine of speciation and cladogenesis (Dodsworth et al, 2016;Clark and Donoghue, 2017;Mandáková and Lysak, 2018).…”
Section: Post-polyploidy Diploidization a Cradle For Diversificationmentioning
confidence: 99%
“…polyploidy) in the origin and subsequent diversification of flowering plants [31][32][33][34][35][36][37]. For example, an ancient polyploidy event has been inferred for the common ancestor of all angiosperms [38,39], three sequential polyploidy events in the monocots pre-date the radiation of the grasses [40,41] and ancient hexaploidy characterizes most eudicots [42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%